(untitled) (Current Horticulture, 2023)
The experiment was conducted at Department of Seed Science and Technology, BACA, AAU, Anand, to find out the effect of fruit retention and days to fruit maturity on seed yield of okra (Abelmoschus esculentus), during kharif season of 2021-22. The experiment consisted of twelve treatment combinations involving four different number of fruits retention, viz. R1: 10 fruits/plant, R2: 15 fruits/ plant, R3: 20 fruits/plant and R4: all fruits/plant and three days to fruit maturity, viz. M1: 50 days after fruit formation, M2: 60 days after fruit formation and M3: 70 days after fruit formation. The 15 fruits retained/plant (R2) and 50 days after fruit formation (M1) gave significantly higher fruit yield, seed quality and seed vigour. The maximum weight of fruit (7.80 g), fruit length (17.77 cm), fruit girth (5.75 cm), number of seeds/fruit (47.01), 100-seed weight (6.893 g), germination (96.67 %), seedling root length (11.91 cm), seedling shoot length (18.68 cm), seedling length (30.58 cm), seedling fresh weight (4.810 g), seedling dry weight (0.1804 g), seedling vigour index-I (2955.96) and seedling vigour index-II (17.44) were noticed in 15 fruits/plant 50 days after fruit formation (R2M1). Whereas, lower (0.800) electrical conductivity was recorded with R2M2.